(untitled) (Kinesiology, 2022)
E-sports can be defined as an electronic sports form and is growing at a rapid pace worldwide. E-sport requires high-speed reactions during all games. The purpose of this study was to evaluate auditory, visual and aim reaction times in different duration of game playing in e-sport players. Fifty-three participants were assigned into two groups according to their playing time which was either more or less than 14 hours per week. The participants were tested for auditory reaction time with online website at playback.fm, visual and aim reaction time on website of humanbenchmark.com. There were statistically significant differences in visual (p<.001) and aim (p<.001) reaction time between the groups, whereas in auditory reaction time no significant difference was found (p=.397). The visual and aim reaction times were higher in the gamers who play more than 14 hours in e-sport. Our study showed that visual and aim reaction time was more affected from game playing time than auditory reaction time in e-sport gamers. Playing e-sport may have positive effects on visual and aim reaction time in young population. Key words: eSports, visual reaction time, aim reaction time, auditory reaction time